Structure and properties of conducting bacterial cellulose-polyaniline nanocomposites - Marins, Jessica A.; Soares, Bluma G.; Dahmouche, Karim; Ribeiro, Sidney José Lima [UNESP]; Barud, Hernane [UNESP]; Bonemer, Denise [UNESP] (Springer, 2011)
Conducting composite membranes of bacterial cellulose (BC) and polyaniline doped with dodecylbenzene sulfonic acid (PAni.DBSA) were successfully prepared by the in situ chemical polymerization of aniline in the presence of hydrated BC sheets. The polymerization was performed with ammonium peroxydisulfate as the oxidant agent and different amounts of DBSA. The composites were characterized by X-ray diffraction, attenuation reflectance Fourier transform infrared spectroscopy, scanning electron microscopy (SEM), impedance spectroscopy and small angle X ray scattering (SAXS). The highest electrical conductivity value was achieved by using a DBSA/aniline molar ratio of 1.5 because this condition provided a better penetration of PAni.DBSA chains inside the hydrated BC sheet, as observed by SEM. The in situ polymerization gives rise to conducting membranes with the surface constituted by different degree roughness as indicated by Nyquist plots obtained from impedance spectroscopy and confirmed by SAXS measurements. This preliminary work provides a new way to prepare cellulose-polyaniline conducting membranes which find potential applications as electronic devices, sensors, intelligent clothes, etc.
Keywords: Bacterial cellulose; Polyaniline; Nano-composite; SAXS; Impedance spectroscopy